The digital identity issue. (August 2015) - Simmonds, Paul
Abstract : We all know that passwords are beyond their sell-by date – the IT industry has been telling us for years, and it seems that recently every week there is the next high-profile hack, with the likes of Sony, Home Depot and Target reported in the past year. In fact, the recent McAfee (Intel Security) report on global cybercrime quotes a conservative estimate of 375bn in losses caused by data breaches, while global credit card fraud, mainly due to identity theft and impersonation, runs in the region of 30bn a year. 1 Passwords are well beyond their 'sell-by' date and attempts to fix the password problem, such as SAML and OAUTH, are not being implemented, mainly because they do not solve key issues. Neither do these solutions address the need to encompass all entities in a single digital identity ecosystem that can work globally. If we are to address all these issues it's time to go back to fundamentals, figure out what is broken and design Identity 3.0 to fix it, says Paul Simmonds of the Global Identity Foundation.